PERAN LEMBAGA ZAKAT DALAM PENGENTASAN KEMISKINAN DI INDONESIA - Syaakir Sofyan (Fakultas Syariah Institut Agama Islam Negeri Palu, 2018)
Zakat is part of Islamic teachings that cover various aspects of human life. The main economic problems related to poverty are the biggest problems in a country's economy. Zakat is able to solve this problem by optimizing all potential in collecting zakat funds. Zakat is believed to be able to contribute greatly in promoting social justice, human development, and alleviating poverty. Therefore, zakat should be managed professionally and productively so that the role and contribution in prospering the community can be achieved. In addition, awareness of Muslims is also needed in efforts to develop the welfare of the people and is also a social responsibility in the welfare of the people who are still in the poverty line.